Actions speak louder than words : community activism as curriculum - Oyler, Celia (London : Routledge, 2012)
How do educators engage students in community action projects without telling them what to think, how to think, or what to do? Is it possible to integrate social justice organizing into the curriculum without imposing one's political views on students? In Actions Speak Louder than Words, longtime activist and teacher educator Celia Oyler delves into such questions through firsthand accounts of social action projects. By moving beyond charity work or volunteerism, she shows how community activism projects offer fertile ground for practicing democratic engagement as part of classroom work
Includes bibliographical references (p. [185]-189) and index
EDU
Keywords: Community and school -- United States; Schools -- Public relations -- United States; Communication in education -- United States